Embryonic Development of Grasshopper Populations Along Latitudinal Gradients Reveal Differential Thermoaccumulation for Adaptation to Climate Warming - Hao, Shuguang; Liu, Chunxiang; Ma, Chuan; Guo, Wei; Kang, Le (Frontiers in Ecology and Evolution, 2021)
Climate warming has a remarkable effect on the distribution, phenology, and development of insects. Although the embryo development and phenology of nondiapause grasshopper species are more susceptible to warming than those of diapause species, the responses of developmental traits in conspecifically different populations to climate warming remain unknown. Here, we compared the mtDNA sequences and egg development of eight populations of grasshopper species (Chorthippus dubius) in field-based manipulated warming and laboratory experiments. The mtDNA sequences showed a significant genetic differentiation of the southernmost population from the other seven populations on the Mongolian Plateau. The warming treatments and incubation at the same location significantly accelerated the egg development of all eight populations, whereas the magnitude of the developmental rate exhibited a northward increase. The egg development of the southernmost population was significantly slower than those of the northern populations at the same incubation temperatures. Interestingly, laboratory experiments showed that a significant difference exists in the effective accumulated degree days (EADDs) but not in the low developmental threshold temperatures (LDTTs) among the different populations. The high-latitude populations had lower EADDs than the low-latitude populations. Multiple linear regressions confirmed that the egg development characteristics of different populations were correlated with the mean annual temperature rather than with the total annual precipitation or photoperiod. The results indicated that grasshopper species have evolved a strategy of adjusting their EADDs but not their LDTTs to adapt to temperature changes. The variations in the EADDs among the different populations enabled the grasshopper eggs to buffer the influences of higher temperatures on development and preserve their univoltine nature in temperate regions while encountering warmer climatic conditions. Thus, the findings of this study highlight the adaptation of nondiapause insects to climate warming through differential thermoaccumulation in egg development.